PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN STRES KERJA TERHADAP KINERJA PERSONIL SATUAN PEMELIHARAAN (SATHAR) 53 DI LANUD ADI SOEMARMO - Ahmi Sazli Joenoes (JI@P, 2022)
The purpose of this study was to determine the effect of leadership style, motivation,and work stress either partially or simultaneously on the performance of Sathar 53personnel at Adi Soemarmo Air Base. This study uses a quantitative method thatfocuses on the type of explanation (explanatory). The population of all Sathar 53personnel is 54 people, and all of them are used as respondents. Data collectiontechniques using a questionnaire. The instrument test uses validity and reliabilitytests. The data analysis technique used was descriptive, multiple linear regression,t test, F test, and coefficient of determination (R²). The results of the validity andreliability test showed that all statements regarding leadership style, motivation,work stress, and personnel performance were valid and reliable. The resultsshowed that the variables of leadership style (X1), motivation (X2) and work stress(X3) partially or simultaneously had a significant effect on the performance ofSathar 53 personnel. The magnitude of the influence of leadership, motivation andwork stress on the performance of Sathar 53 personnel was 43.5 % and theremaining 56.5% is influenced by other variables not examined. Keywords: Leadership Style, Motivation, Work Stres, Performance